- #1

- 654

- 2

## Main Question or Discussion Point

ok .lets say the expression we have is e

the taylor expansion becomes 1+x+x

integrating becomes x+x

so how do we know that c = 1? for it to become back to e

becos it is said that integral of e

do we just let x be 0 to find c = 1? does it work for all expressions?

thanks a lot!

^{x}the taylor expansion becomes 1+x+x

^{2}/2+...integrating becomes x+x

^{2}/2+x^{3}/6+...+cso how do we know that c = 1? for it to become back to e

^{x}becos it is said that integral of e

^{x}= e^{x}do we just let x be 0 to find c = 1? does it work for all expressions?

thanks a lot!